2019
DOI: 10.1186/s12882-019-1394-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of anisodamine in rats with glycerol-induced acute kidney injury

Abstract: Background Anisodamine is used for the treatment of reperfusion injury in various organs. In this study, we investigated the effectiveness and mechanisms of action of anisodamine in promoting recovery from glycerol-induced acute kidney injury (AKI). Methods We compared the protective effects of atropine and anisodamine in the rat model of glycerol-induced AKI. We examined signaling pathways involved in oxidative stress, inflammation and apoptosis, as well as expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 40 publications
6
30
0
Order By: Relevance
“…The specific mechanism may be by reducing the expression of ER stress markers IRE-1α, CHOP and ATF4, and inhibiting the activation of TXNIP and NLRP3 inflammasome. 11,26 Besides, ANI protected against myocardial ischemia/reperfusion (I/R) injury. Further mechanism analysis showed that the role of ANI in myocardial I/R may be by the inhibition of oxidative stress, inflammatory factors and cardiomyocyte apoptosis via Figure 5 ANI regulates the levels of inflammatory cytokines by inhibiting NLRP3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The specific mechanism may be by reducing the expression of ER stress markers IRE-1α, CHOP and ATF4, and inhibiting the activation of TXNIP and NLRP3 inflammasome. 11,26 Besides, ANI protected against myocardial ischemia/reperfusion (I/R) injury. Further mechanism analysis showed that the role of ANI in myocardial I/R may be by the inhibition of oxidative stress, inflammatory factors and cardiomyocyte apoptosis via Figure 5 ANI regulates the levels of inflammatory cytokines by inhibiting NLRP3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…4) Anisodamine and organs protection: Anisodamine had displayed wide protection in other important organs, which were also affected in the COVID-19 infection. For example, anisodamine had cardioprotective effect through the suppression of cardiomyocytes apoptosis ( 67 ), protected against ischemic stroke via the α7nAChR ( 68 ), ameliorated renal dysfunction by reducing oxidative stress, the inflammatory response and cell death ( 69 ). The α7nAChR is widely distributed in these organs.…”
Section: Recommended Approaches That Activate Cap In Covid-19 Infectimentioning
confidence: 99%
“…Images were acquired with an Olympus DP70 microscopy with a digital camera (Olympus Optical Co, Ltd., Tokyo, Japan). Using ImageJ software v.1.52s (National Institutes of Health, U.S.A.), the swelling, vacuolar degeneration, necrosis and desquamation of tubular epithelial cells were graded using a semi-quantitative scoring method as previously described [13]…”
Section: Histopathologic Evaluationmentioning
confidence: 99%
“…In mice with Shiga toxin-producing Escherichia coli infection, anisodamine administration suppressed TNF-α mRNA expression [12]. In glycerol-induced AKI, anisodamine administration reduced ROS-induced oxidative stress and thus protected against AKI [13]. Therefore, we hypothesized that the natural extract AniHBr prevent kidney from septic injury by suppressing the mitochondrial metabolism and subsequently mitochondrial dysfunction via suppression of oxidative stress and release of inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%